Exploring Challenges and Strategies in Partnering With Community-Based Organizations to Advance Intervention Development and Implementation With Older Adults. (27th December 2021) - Nkimbeng, Manka; Han, Hae-Ra; Szanton, Sarah L; Alexander, Kamila A; Davey-Rothwell, Melissa; Giger, Jarod T; Gitlin, Laura N; Joo, Jin Hui; Koeuth, Sokha; Marx, Katherine A; Mingo, Chivon A; Samuel, Laura J; et al.
Abstract: Minoritized older adults face multiple health inequities and disparities, but are less likely to benefit from evidence-based health care interventions. With the increasing diversity of the U.S. aging population, there is a great promise for gerontology researchers to partner with racial/ethnic minority organizations and underrepresented communities to develop and implement evidence-based health interventions. Community-Based Participatory Research and Implementation Science offer guidance and strategies for researchers to develop and sustain community partnerships. However, researchers partnering with community organizations continue to face challenges in these collaborations, study outcomes, and sustainability. This may be especially true for those junior in their career trajectory or new to community-engaged research. The purpose of this forum article is to detail critical challenges that can affect gerontology researcher–community partnerships and relationships from the perspective of researchers. Seven challenges (pre- or mid-intervention design, implementation, and postimplementation phases) described within the Equity-focused Implementation Research for health programs framework are identified and discussed. Potential solutions are also presented. Planning for potential obstacles of the researcher–community partnerships can inform innovative solutions that will facilitate successful partnerships, thereby promoting the advancement of collaborative research between academic institutions and community organizations to improve older adult health outcomes.